2017
DOI: 10.1016/j.appet.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual food cues decrease postprandial glucose concentrations in lean and obese men without affecting food intake and related endocrine parameters

Abstract: The abundance of highly palatable food items in our environment represents a possible cause of overconsumption. Neuroimaging studies in humans have demonstrated that watching pictures of food increases activation in brain areas involved in homeostatic and hedonic food cue processing. Nevertheless, the impact of food cues on actual food intake and metabolic parameters has not been systematically investigated. We tested the hypothesis that watching high-calorie food cues increases food intake and modifies antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The consequences of the upregulation of insulin, GIP and GLP-1 in response to visual food cues are well reflected in terms of the differences in blood glucose levels. Particularly in study I, in which we observe a trend in glucose levels indicating the difference between the S and NS day 15 minutes after the exposure to pictures (11:30 am), confirming previous report [78]. Therefore, we propose a model in which food cues provoke GIP and GLP-1 secretion.…”
Section: Plos Onesupporting
confidence: 90%
“…The consequences of the upregulation of insulin, GIP and GLP-1 in response to visual food cues are well reflected in terms of the differences in blood glucose levels. Particularly in study I, in which we observe a trend in glucose levels indicating the difference between the S and NS day 15 minutes after the exposure to pictures (11:30 am), confirming previous report [78]. Therefore, we propose a model in which food cues provoke GIP and GLP-1 secretion.…”
Section: Plos Onesupporting
confidence: 90%
“…However, Kunath et al [ 90 ] did not find any evidence for the potential of ghrelin acting as a short-term cognitive enhancer in humans. It has been found that viewing food pictures does not affect total calorie intake and ghrelin levels, but improves postprandial glucose levels [ 91 ].…”
Section: Ghrelin Influences the Hedonic And Incentive Responses To Comentioning
confidence: 99%
“…In our study, both groups presented a decreased in insulin, glucose, and cortisol levels after the fMRI task. Thus, the effects of fasting might have potentially surpassed the effects of stimulation with food pictures (Brede et al, 2017). Nonetheless, this hypothesis needs further testing.…”
Section: Discussionmentioning
confidence: 99%